2015
DOI: 10.1155/2015/158012
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Dynamic Characteristic of Acupoints Based on the Primary Dysmenorrhea Patients with the Tenderness Reflection onDiji(SP 8)

Abstract: In TCM theory, acupoint is not a fixed point but a portal with dynamic characteristics where the channel qi enters and flows out. The dynamic characteristics have been verified primarily by detecting the tenderness reaction on Diji (SP 8) in primary dysmenorrhea patients. In this study, finger pressing and algometer were applied in Diji (SP 8) area of participants in menstrual period and nonmenstrual period, respectively, to detect the tenderness occurrence rate, the VAS score of the tenderest point, the tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…It is worthwhile pointing out that the location and functional status of acupoints are considered dynamic within a certain range of time and space, varying with different physiological and pathological conditions [ 6 7 ]. It has also been reported that MCs not only induce a neuro-immuno response by the release of inflammatory mediators following acupuncture; they also play a crucial role in the cross-talk among the circulatory, nervous and immune networks at acupoints [ 8 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worthwhile pointing out that the location and functional status of acupoints are considered dynamic within a certain range of time and space, varying with different physiological and pathological conditions [ 6 7 ]. It has also been reported that MCs not only induce a neuro-immuno response by the release of inflammatory mediators following acupuncture; they also play a crucial role in the cross-talk among the circulatory, nervous and immune networks at acupoints [ 8 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pressure pain threshold (PPT) is a semiobjective method used to quantify localised pain 22 23. Clinical studies have confirmed that the sensitivity (PPT) at acupoints changes when patients are in a diseased state, such as shoulder pain,24 knee osteoarthritis,25 primary dysmenorrhea26 and premenstrual syndrome 27. The degree of change in the PPT may objectively reflect the intensity of acupoint sensitisation and it may be related to the disease status 28.…”
Section: Introductionmentioning
confidence: 99%
“…Some are located in the pathological local areas: in patients with gastric ulcer, pressure-pain threshold (PPT) was found to be decreased significantly on Burong (ST19) and Liangmen (ST21), which are located on the anterior abdomen [29]. It was further reported that pain- and heat-sensitized acupoints were also located in distal areas along the corresponding meridians [30, 35, 40, 41] or bilateral sides of the spine in diseases like allergic rhinitis, lumbar disc herniation, and asthma [38, 39, 42]. Beyond this, some sensitized acupoints have been reported as extra acupoints (they are not on the 14 recognized meridians but have specific names, locations, related diseases, and clinical usage) under certain conditions.…”
Section: Resultsmentioning
confidence: 99%